Pengaruh Motivasi, Kompensasi, dan Disiplin Kerja Terhadap Prestasi Kerja Karyawan Di Puri Sebali Resort & Spa Gianyar - Susanto, I Komang Putra; Dian Maha Yoga, Gede Agus (WidyaAmrita: Jurnal Manajemen, Kewirausahaan dan Pariwisata, 2021)
Job performance in a company is a very important element. Through optimal use of human resources, it will be able to improve employee performance. Employee performance is influenced by several factors such as motivation, compensation and work discipline. The formulation of the problems and objectives in this study were to determine the effect of motivation, compensation and work discipline on work performance. The research location is at Puri Sebali Resort & Spa Gianyar with a sample of 40 respondents. Data collection methods used observation, interviews, documentation study and questionnaires, data analysis techniques used validity, reliability, classical assumptions, multiple linear regression, coefficient of determination, t test and F test. Based on the research results, the results obtained: (1) motivation has a significant positive effect on work performance, the t value is 2.090 and 0.044 sig. (2) compensation has a significant positive effect on work performance, the t value is 2.054 and sig 0.047. (3) work discipline has a significant positive effect on work performance, the t value is 2.064 and 0.046 sig. (4) simultaneously the independent variable has a significant effect on work performance, the value of F is 14.781 and a significance of 0.000. The magnitude of the influence of the independent variables on work performance is 51.5%. The suggestion in this research is that Puri Sebali Resort & Spa Gianyar is expected to give a warning or sanction to employees who often waste time at work, be fair to employees, provide training to employees.